Phosphokinase Antibody Arrays on Dendron-Coated Surface - Kwak, Ju-Won (Public Library of Science, 2014)
Monitoring protein phosphorylation at the cellular level is important to understand the intracellular signaling. Among the phosphoproteomics methods, phosphokinase antibody arrays have emerged as preferred tools to measure well-characterized phosphorylation in the intracellular signaling. Here, we present a dendron-coated phosphokinase antibody array (DPA) in which the antibodies are immobilized on a dendron-coated glass slide. Self-assembly of conically shaped dendrons well-controlled in size and structure resulted in precisely controlled lateral spacing between the immobilized phosphosite-specific antibodies, leading to minimized steric hindrance and improved antigen-antibody binding kinetics. These features increased sensitivity, selectivity, and reproducibility in measured amounts of protein phosphorylation. To demonstrate the utility of the DPA, we generated the phosphorylation profiles of brain tissue samples obtained from Alzheimer's disease (AD) model mice. The analysis of the profiles revealed signaling pathways deregulated during the course of AD progression.